The Impact of Pore Structure on Kerogen Geomechanics. (15th September 2021) - Alafnan, Saad
Abstract : Production stimulation techniques such as the combination of hydraulic fracturing and lateral drilling have made exploiting unconventional formations economically feasible. Advancements in production aspects are not always in lockstep with our ability to predict and model the extent of a fracturing job. Shale is a clastic sedimentary rock composed of a complex mineralogy of clay, quartz, calcite, and fragments of an organic material known as kerogen. The latter, which consists of large chains of aromatic and aliphatic carbons, is highly elastic, a characteristic that impacts the geomechanics of a shale matrix. Following a molecular simulation approach, the objective of this work is to investigate kerogen's petrophysics on a molecular level and link it to kerogen's mechanical properties, considering some range of kerogen structures. Nanoporous kerogen structures across a range of densities were formed from single macromolecule units. Eight units were initially placed in a low-density cell. Then, a molecular dynamic protocol was followed to form a final structure with a density of 1.1 g/cc; the range of density values was consistent with what has been reported in the literature. The structures were subjected to petrophysical assessments including a helium porosity analysis and pore size distribution characterization. Mechanical properties such as Young's modulus, bulk modulus, and Poisson ratio were calculated. The results revealed strong correlations among kerogen's mechanical properties and petrophysics. The kerogen with the lowest porosity showed the highest degree of elasticity, followed by other structures that exhibited larger pores. The effect temperature and the fluid occupying the pore volume were also investigated. The results signify the impact of kerogen's microscale intricacies on its mechanical properties and hence on the shale matrix. This work provides a novel methodology for constructing kerogen structures with different microscale properties that will be useful for delineating fundamental characteristics such as mechanical properties. The findings of this work can be used in a larger scale model for a better description of shale's geomechanics.